2023
DOI: 10.3390/aerospace10030283
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonised Future Regional Airport Infrastructure

Abstract: Sustainability and, especially, emission reductions are significant challenges for airports currently being addressed. The Clean Sky 2 project GENESIS addresses the environmental sustainability of hybrid-electric 50-passenger aircraft systems in a life cycle perspective to support the development of a technology roadmap for the transition to sustainable and competitive electric aircraft systems. This article originates from the GENESIS research and describes various options for ground power supply at a regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A 60 kW five-phase IPMSM was reported in [48] achieving 3.12 kW/kg. A six-phase electric aircraft motor was assessed in [37], resulting in 10.6 kW/kg for active parts (6.4 kW/kg considering total weight). Additionally, Da Rosa and others [11] and Fleitas and others [19] showed that a multi-phase machine may not differ in mass from the three-phase machine and can even have a lower value, due to the lower volume of conductive material required.…”
Section: Proposed Alternative Topologiesmentioning
confidence: 99%
“…A 60 kW five-phase IPMSM was reported in [48] achieving 3.12 kW/kg. A six-phase electric aircraft motor was assessed in [37], resulting in 10.6 kW/kg for active parts (6.4 kW/kg considering total weight). Additionally, Da Rosa and others [11] and Fleitas and others [19] showed that a multi-phase machine may not differ in mass from the three-phase machine and can even have a lower value, due to the lower volume of conductive material required.…”
Section: Proposed Alternative Topologiesmentioning
confidence: 99%
“…The generated LCI datasets covered technologies required to explore different aircraft configurations and technology advances in energy supply and storage for three time horizons. Technology foresight assessments and analyses of top-level aircraft requirements were conducted in the GENESIS project to identify relevant energy technologies in 2030 (short-term), 2040 (medium-term), and 2050+ (long-term) time horizons (see Marciello et al (2023) and Meindl et al (2023a)). Propulsion systems in scope include internal combustion engines (ICE, with the supply of conventional or AAF), batteries, fuel cells, and a combination of those (Marciello et al, 2023).…”
Section: Overview Of Technologies Addressedmentioning
confidence: 99%
“…Therefore, in the absence of detailed knowledge, the Combined Charging System (CCS) standard limits for electric vehicles were used as starting point, which is the preferred charging standard in Europe and North America (Abogdallah, 2023). In all time horizons, the charging station was designed to charge hybrid aircraft with batteries in 45 min (Meindl et al, 2023a(Meindl et al, , 2023c. The progress of technology was modeled assuming a functioning at 600 V and 500 kW in 2030 and 1200-1300 kW in 2040 and 2050 (Meindl et al, 2023a).…”
Section: Battery Charging Stationmentioning
confidence: 99%
See 2 more Smart Citations